2018
DOI: 10.1080/17453674.2018.1518570
|View full text |Cite
|
Sign up to set email alerts
|

Higher mid-term revision rates of posterior stabilized compared with cruciate retaining total knee arthroplasties: 133,841 cemented arthroplasties for osteoarthritis in the Netherlands in 2007–2016

Abstract: Background and purpose — The preference for a cruciate retaining (CR) or posterior stabilized (PS) TKA (total knee arthroplasty) system varies greatly between Dutch hospitals, independent of patient characteristics. We examined mid-term revision rates for men and women of different age categories.Patients and methods — We included all 133,841 cemented fixed-bearing primary CR or PS TKAs for osteoarthritis reported in the Dutch Arthroplasty Register (LROI) in 2007–2016. Revision procedures were defined as minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…The revision was categorized as non‐patellar (i.e., due to tibia or femoral‐related complications) and patellar revisions (due to patellar‐related complications), as referenced in a previous study 2 . Patellar resurfacing was associated with reduced non‐patellar and patellar revisions, in line with an investigation in the Netherlands 74 and previous meta‐analysis 2,4–13,75 . In our analysis, the number needed to treat (NNT) to prevent one revision was 13 knees, compared to 25 in Teel's study 5 .…”
Section: Discussionsupporting
confidence: 87%
“…The revision was categorized as non‐patellar (i.e., due to tibia or femoral‐related complications) and patellar revisions (due to patellar‐related complications), as referenced in a previous study 2 . Patellar resurfacing was associated with reduced non‐patellar and patellar revisions, in line with an investigation in the Netherlands 74 and previous meta‐analysis 2,4–13,75 . In our analysis, the number needed to treat (NNT) to prevent one revision was 13 knees, compared to 25 in Teel's study 5 .…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is quite uncertain whether these differences influence long-term migration, which should be further investigated, such as by assessing migration using certain feature points of the implant (e.g., medial border of the tibial component). However, minor changes in TKA design could have clinical effects as a recent study comparing revision rates of CR designs with PS designs in the Dutch arthroplasty registry found that PS designs had higher revision rates (28).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, according to whether the posterior cruciate ligament is preserved, there are two kinds of prostheses, including posterior CR prostheses and posterior cruciate-stabilized prosthesis (PS) [60, 61]. The CR prosthesis can better simulate the rolling mechanism and biomechanical characteristics of the normal knee, and achieve higher proprioceptive sensation [28].…”
Section: Discussionmentioning
confidence: 99%